Martin Bulmer and race and ethnic studies. Issue 8 (11th June 2022) - Solomos, John
ABSTRACT: This contribution to the symposium focuses on those facets of Martin Bulmer's work that sought to analyse the role of race and ethnicity in the development of sociological research. It highlights, in particular, his continuing interest through much of his scholarship with the work of the Chicago School and of key figures within it in the development of both conceptual and empirical research agendas in this field. This interest was intimately linked to his long-standing curiosity about the origins of sociological research and the links between sociology and social and public policy. The paper also explores Bulmer's engagement with questions about race and ethnicity. It also highlights his contribution to the development of the journal Ethnic and Racial Studies as a key forum for the publication of empirical and theoretical research on race and ethnic issues, linking the contributions of diverse national scholarly traditions together.